2011
DOI: 10.1021/am2008536
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Examination of Nanoparticle Heating Kinetics Upon Near Infrared (NIR) Irradiation

Abstract: Near infrared (NIR) light, which spans wavelengths from ~700-1100 nm holds particular promise in bionanotechnology-enabled applications because both NIR light and nanoparticles (NPs) have the potential for remote activation leading to exquisite localization and targeting scenarios. In this study, aqueous solutions of carbon and metal-based NPs (carbon black, single-walled carbon nanotubes, silver nanoparticles and copper nanoparticles) were exposed to continuous NIR laser (λ = 1064 nm) irradiation at powers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…[5][6][7] Magnetite (Fe 3 O 4 ) nanoparticles induce local hyperthermia when subject to a near infrared (NIR) optical source. 1,8,9 This hyperthermic effect alone may provide the required thermal energy to ablate local tissue but also may act as a triggering mechanism for release of chemotherapeutics trapped within a polymer matrix surrounding the nanoparticles, 5,8,10 and provide a protective to attenuate the toxicity of uncoated magnetite 11,12 . Previous literature has been largely aimed at the ablation of in-vitro cultures without laser attenuation 6,8 or of subcutaneous tumors with minimal attenuation from biological tissue.…”
mentioning
confidence: 99%
“…[5][6][7] Magnetite (Fe 3 O 4 ) nanoparticles induce local hyperthermia when subject to a near infrared (NIR) optical source. 1,8,9 This hyperthermic effect alone may provide the required thermal energy to ablate local tissue but also may act as a triggering mechanism for release of chemotherapeutics trapped within a polymer matrix surrounding the nanoparticles, 5,8,10 and provide a protective to attenuate the toxicity of uncoated magnetite 11,12 . Previous literature has been largely aimed at the ablation of in-vitro cultures without laser attenuation 6,8 or of subcutaneous tumors with minimal attenuation from biological tissue.…”
mentioning
confidence: 99%
“…37 A schematic [ Fig. The power was set to 12% of maximum power and then aligned through two 70 T/ 30 R beam splitters.…”
Section: F Near-infrared Lasermentioning
confidence: 99%
“…Complementary strand DNA (csDNA) chains prelabeled with ferrocennecarboxaldehyde (FCA), i.e., [FCA-C6]ACCAGTTGGTCTGGTGTCAA-3 0 , were then used for hybridizing with the surface-immobilized oligonucleotides to form double strand DNA (dsDNA) helices. [34][35][36][37] However, some studies are beginning to utilize hybrid combinations of gold and CNTs (Refs. 6,10,11 In this case, the final hybrid nanostructures are attractive candidates for the next generation, hybrid functional nanosystems due to a combination of extraordinary strength, unique optical properties, efficient heat conduction, high binding affinity for biomolecules, chemical stability, and overall robustness.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical, thermal and spectral properties of SWNTs have been used to develop a number of new technologies for the detection, monitoring and therapy of diseases including cancer [1][2][3][4]. Although pulmonary toxicity of commercially sourced SWNTs was reported when administrated by direct intratracheal instillation [5], it was found that SWNTs were non-toxic to the experimental mice when administrated intravenously and only mild local inflammatory reactions were observed following implantation of SWNTs [6].…”
Section: Introductionmentioning
confidence: 99%